Leadership styles and practices of senior leaders in school settings - Shariman, Suriani; Syariff M. Fuad, Dayang Rafidah (Journal of Islamic, Social, Economics and Development, 2025)
School leadership shapes teaching, learning, and the daily life of a school. It sets direction, supports staff, and holds the routine steady when change arrives. Yet the same role looks different across places and times, and no single model fits all schools. This concept paper explores how leadership styles such as transformational, instructional, distributed, inclusive, and strategic, connect to the concrete practices that senior leaders use, like mentoring teachers, supervising instruction, using data, and building trust with families and communities. The focus is on senior leaders in school settings and on how styles become practices that influence outcomes for teachers, students, and the wider school culture. The paper draws only on past studies to build a clear conceptual argument, blending evidence from multiple countries and contexts (Harris & Jones, 2023; Abdullah, Razak, & Hoque, 2022; Parveen, Quang Bao Tran, Kumar, & Shah, 2022; Esia‑Donkoh & Quansah, 2021). It does not report findings from new fieldwork. Instead, it offers an integrated discussion that shows why leaders rarely rely on a single style and how they mix approaches to match local need (Agyeman & Aphane, 2024; Tawiah, 2022). The contribution is a simple, usable way to think about linkage: leadership styles guide the mindset, leadership practices carry the action, and together they shape school outcomes (Adams, Mohamed, Moosa, Shareefa, & Tan, 2025; Berhanu, 2025; Barth & Tsemach, 2025). The paper proposes a conceptual path that can inform leadership standards, training, and future research design, while keeping attention on cultural fit and system goals in places like Malaysia and across the Global South (Abdullah et al., 2022; Kunalan, Ali, Ibrahim, & Sidek, 2022; Vorontsova & Dakhari, 2024).